Incidence, Predictors, and Strategies for Retrograde Wire Tracking Failure via Poor Septal Collateral Channels in Chronic Total Occlusion - Wang, Cheng-Fu; Chen, Bao-Jun; Luan, Bo; Wang, Yong; Zhang, Xiao-Jiao; Qu, Hai-Bo (Clinical interventions in aging, 2023)
Background: Retrograde guidewire (GW) tracking success via a poor septal collateral channel (CC) when an antegrade approach fails is crucial for successful revascularization of coronary chronic total occlusion (CTO) with poor septal CC. However, the incidence, predictors, and management strategies for retrograde GW tracking failure via poor septal CC remain unclear. Methods: In total, 122 CTO patients who underwent retrograde septal percutaneous coronary intervention (PCI) with poor CC between January 2017 and May 2022 were retrospectively analyzed. Patients were divided into the retrograde GW tracking success group (success group) and the retrograde GW tracking failure group (failure group). Clinical and angiographic data were compared to investigate the predictors of retrograde GW tracking failure. Results: The incidence of GW tracking failure was 22.1% (27/122). Patients in the failure group had a higher prevalence of left anterior descending artery (LAD) CTO (66.7% vs 37.9%; p = 0.009) and a higher incidence of well-developed non-septal collateral (66.7% vs 30.5%; p = 0.001). Patients witha septal CC diameter [greater than or equal to] 1 mm (48.1% vs 70.5%; p = 0.040), [greater than or equal to] 3 septal CCs (44.4% vs 66.3%; p = 0.046), and initial retrograde application of Guidezilla (37.0% vs 60.0%; p = 0.048) were significantly lower in the failure group than in the success group. The binary logistics regression model showed that a CC diameter < 1 mm, well-developed non-septal collateral, and LAD CTO were independent predictors for GW tracking failure in patients undergoing retrograde CTO PCI via poor septal CC. Conclusion: The success rate of retrograde GW tracking via poor septal CC was high, with a relatively high procedural success rate. A CC diameter < 1 mm, well-developed non-septal collateral, and LAD CTO were independent predictors of GW tracking failure in patients undergoing retrograde CTO PCI via poor septal CC. Keywords: coronary chronic total occlusion, retrograde, PCI, septal collateral channels